Pengembangan Materi Bimbingan dan Konseling Klasikal Bidang Belajar di Sekolah Menengah Pertama - Ika Ariyati; Nurul Aisyah (Bulletin of Counseling and Psychotherapy, 2022)
This research aims to produce classical guidance materials (academic) that are appropriate with needs of students and proper to use. The research and development of the materials were adapted from the Borg and Gall’s development model completed until the seventh stage. Needs analysis in this study applied a need assessment topic of guidance and counselling (academic) given to 358 students of class VIII from 16 Public Junior High Schools (SMP) in Yogyakarta City. The validators in this research consisted of two experts of materials and ten practitioners. The data collection instrument given to the experts and practitioners used an assessment sheet questionnaire. All obtained data were analysed quantitatively and qualitatively. The results of this research indicated that there were ten topics of priority materials needed by the students. The ten topics of materials were validated by the experts and the practitioners of guidance and counselling. The validation results by two experts of guidance and counselling and five practitioners were included in very good category with an average score of 92.83%. Results of a trial limited to ten teachers of guidance and counselling on the materials obtained an average score of 97.76% indicating very good category. Therefore, this study indicated that the materials developed were in accordance with the need assessment which are appropriate to be used as a support system in guidance and counselling services.